Capacitating Science-Policy dialogue platforms to trigger actions for accessing climate finance: experiences and lessons learnt from Ghana, Mali and Niger - Segnon, Alcade C; Botchway, Vincent Ansah; Sogoba, Bougouna; Idrissa, Mamoudou; Moglo, Komlanvi; Samaké, Oumar; Essegbey, George Owusu; Karbo, Naaminong; Whitbread, Anthony M.; Thornton, Philip K.; Zougmoré, Robert B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Adequate financial resources are key barriers limiting the effectiveness and sustainability of the national science-policy dialogue platforms in West Africa. This Info Note documents the outcomes of and lessons learnt from capacity building activities to science-policy dialogue platforms in Ghana, Mali and Niger and how the capacity building program empowered the platforms and/or triggered actions for accessing climate finance. A structured engagement and capacity building approach was implemented to strength resource mobilization capacity of the science-policy dialogue platforms in Ghana, Mali and Niger. The approach has enabled the development of three GCF concept notes and two bilateral donor proposals for accessing climate finance. The structured engagement and capacity building approach adopted was instrumental in triggering actions. The strong commitment and leadership of the institutions hosting the secretariat of the platforms were also crucial in triggering actions